Urate oxidase from tea microbe Colletotrichum camelliae is involved in the caffeine metabolism pathway and plays a role in fungal virulence - He, Shengnan; Qiao, Xiaoyan; Zhang, Shuhan; Xia, Jinglin; Wang, Lei; Liu, Shouan (Frontiers in Nutrition, 2023)
Tea is one of the most well-known, healthy beverages in the world. Tea plants produce caffeine as a secondary metabolite. Colletotrichum camelliae is one of the most important microbes frequently isolated from tea fields, and it causes anthracnose disease in tea plant. Upon infection of tea plant with C. camelliae, we observed alterations in the expression of fungal transcripts, including those of many genes associated with caffeine metabolism, such as those encoding various transporters, xanthine dehydrogenase, and urate oxidase (UOX). In particular, the deletion of C. camelliae urate oxidase (CcUOX), which is involved in the caffeine metabolism pathway, reduced fungal tolerance to caffeine, and impaired fungal virulence. CcUOX is involved in caffeine metabolism by the degradation of uric acid contents. C. camelliae ΔCcUOX mutants impaired uric acid degradation in vivo. The CcUOX gene was cloned from C. camelliae, overexpressed in Escherichia coli, and the recombinant CcUOX protein displayed maximum activity at 30°C and a pH of 4.0. The recombinant CcUOX efficiently reduced uric acid in vitro suggesting a promising application in caffeine-contaminated environment management and in producing food with low purine contents to prevent uric acid related human diseases, such as hyperuricemia and gout.